Documentary Content in The Digital Era (Watchdoc Documentary Content Study) - Sisca T. Gurning; IGP Wiranegara; Dias Suminta (Metacommunication: Journal of Communication Studies, 2024)
The rise of internet technology has revolutionized how we access media, making it more accessible and affordable for individuals from all walks of life. With the advent of broadcasting tools such as cameras, even ordinary people can create news content, including journalism. Watchdoc production house has taken a unique approach to disseminating information by presenting it as documentary content instead of relying on traditional journalistic channels. This approach helps educate the public about issues often overlooked by mainstream television channels, which are often controlled by authorities. This study explores how the Watchdoc production house selects its documentary content in this information age. It draws on a descriptive qualitative research method that includes literature reviews and interviews. The research findings suggest that the selection of documentary content still holds significant sway and resonates with a broad audience. Furthermore, it addresses the public's disillusionment with traditional journalism, which frequently needs to cover issues affecting marginalized groups.